In silico study of lutein as anti-HER-2 receptors in breast cancer treatment - Cahyani, Ni Ketut Nitya; Putri, Wahyu Nadi Eka; Dwivayana, I Kadek Diva; Mirayanti, Ni Putu Dinda; Laksmiani, Ni Putu Linda (Pharmacy Reports, 2021)
Human Epidermal Receptor-2 (HER-2) overexpression is implicated in breast cancer progression; thus, HER-2 is widely used as the target of anticancer therapy. Lapatinib is a drug widely used to inhibit the HER-2 receptor and tyrosine kinase; however, it develops drug resistance. Lutein is promising to be developed as breast cancer therapy. This study aims to determine the mechanism of inhibition of HER-2 receptor overexpression by lutein in silico. Molecular docking was carried out by optimizing the lutein and lapatinib, preparing of protein target HER-2 (PDB ID 3PP0), validating of molecular docking protocol, and docking of lutein and lapatinib on HER-2. The study resulted in the binding energy of -12.37 kcal/mol, while the binding energy of the native ligand and lapatinib to HER-2 was -10.43 kcal/mol and -12.25 kcal/mol, respectively. The binding energy showed that lutein has potential as breast anticancer suggested from the stronger affinity to HER2.